Marketing Strategy Analysis at Karmens'eve Cafe in Increasing Sales Volume - Ega Dhija Ditriyo; Farida, Siti Ning (MSJ : Majority Science Journal, 2024)
Marketing strategy is a crucial component in business management because it has a direct effect on sales volume. Karmens'eve Cafe, known for its friendly service and cozy atmosphere, shows that the implementation of the right marketing strategy can significantly increase sales. This study uses SWOT analysis to describe Karmens'eve's position in the market. The café's strengths include its strategic location, calm atmosphere, high product quality, and friendly service. However, there are drawbacks such as limited resource management and marketing. On the other hand, the opportunities that exist include the trend of increasing public interest in cafes and the potential of digital marketing that has not been fully utilized. The threat of fierce competition and changing consumer tastes also needs to be watched out. The results of the analysis show that Karmens'eve Cafe has successfully implemented an effective marketing strategy, so that it can continue to increase its sales volume by taking advantage of existing strengths and opportunities.